Working in Kindergarten through the Eyes of Preschool Education Teachers - Motives for Choosing the Profession, Daily Experiences, Needs - Magdalena Bartoszewicz (Maria Curie-Skłodowska University, Lublin, Poland, 2023)
Introduction: The work of teachers is of social importance, especially in the field of pre-school education. Teachers play a key role in shaping the development and skills of the youngest children, supporting their social, emotional and cognitive abilities. A good teacher is not only an expert in his or her field, but also a responsible person who promotes values and acts as a guide in the learning process. Unfortunately, the teaching profession is often portrayed incorrectly, leading to an underestimation of its prestige andinacurate perception of its role, negatively affecting the authority of teachers. Research objective: The aim of the study was to find out the motives for choosing the profession of preschool education teacher and to recognize the daily experiences of female preschool education teachers in their preschool work. Research method: The research was conducted in a qualitative stream, using an in-depth interview - on a group of six female pre-service education teachers. Results: The analysis of the survey results provided insights into the motives for choosing the teaching profession and important areas of daily work in the kindergarten, as well as key challenges. Conclusions: The results of the study lead to the conclusion that working in the teaching profession is a job of choice. On the other hand, the observed challenges in the work of female pre-service teachers lead to feelings of lower job satisfaction. The fact that the teaching profession is increasingly undervalued socially also contributes to this.